Mechanical durability of solid oxide fuel cell glass-ceramic sealant/steel interconnect joint under thermo-mechanical cycling. (August 2019) - Lin, Chih-Kuang; Chen, Kun-Yi; Wu, Si-Han; Shiu, Wei-Hong; Liu, Chien-Kuo; Lee, Ruey-Yi
Abstract: A testing method is developed to quantitatively determine the thermo-mechanical cycling life in oxidizing atmosphere for the joint between a solid oxide fuel cell glass-ceramic sealant and a ferritic stainless steel interconnect. Thermo-mechanical cycling tests are performed under cyclic shear or tensile loading in conjunction with cyclic temperature variance between 40 °C and 800 °C. Results reveal thermo-mechanical cycling life under both shear and tensile loadings increases with a decrease in end stress at 800 °C, for a certain end stress at 40 °C. Nevertheless, for a certain end stress at 800 °C, the tensile thermo-mechanical cycling life increases with a decrease in end stress at 40 °C, while the shear thermo-mechanical cycling life is independent of end stress at 40 °C. A difference in fracture pattern is also observed between shear and tensile loadings. For shear loading, fracture mainly takes place along the interface between glass-ceramic sealant and an oxide layer, such as BaCrO4 or Cr2 O3 . However, for tensile loading, fracture mainly occurs within the glass-ceramic layer, following crack initiation at the interface of Cr2 O3 /sealant or Cr2 O3 /BaCrO4 . Highlights: A thermo-mechanical cycling (TMC) test technique at 40–800 °C is developed. TMC life of SOFC sealant/interconnect joint is quantitatively assessed. TMC life under shear load is controlled only by end stress applied at 800 °C. Both end stresses applied at 40 °C and 800 °C affect TMC life under tensile load. Life trend difference between shear and tensile loads is ascribed to failure mode.